STUDENT ENGAGEMENT IN CHEMISTRY SUPPLEMENTAL INSTRUCTION: Representations of Learning Spaces - Paideya, Vinodhani; Sookrajh, Reshma (South African Journal of Higher Education, 2018)
The Engineering faculty at the University in KwaZulu Natal has a rich diversity of first year engineering students who present themselves as under-prepared for tertiary study as many students have not yet developed the abstract reasoning skills that allow them to learn new ideas simply by reading a text or listening to a lecture. Supplemental Instruction (SI) was thus introduced as a support programme for the first year engineering students. The focus of this article is to theorise the engineering student’s engagement within the SI learning space. This is done using concepts of relate, create and reflect adapted from theories of engagement postulated by Kearsley & Shneiderman (1999) and Leithwood, McAdie, Bascia, & Rodrigue (2006). The findings suggest that social learning spaces encouraged explanations, conceptual understanding and reflective thinking. In theorising engineering student’s engagement within the SI learning space, it is argued that the notion of engagement created representations of physical, cognitive and safe cultural spaces for learning chemistry.